Estimation of PM2.5 Mass Concentration from Visibility - Denghui Ji; Zhaoze Deng; Xiaoyu Sun; Liang Ran; Xiangao Xia; Disong Fu; Zijue Song; Pucai Wang; Yunfei Wu; Ping Tian; Mengyu Huang (Advances in Atmospheric Sciences, 2020)
Aerosols in the atmosphere not only degrade visibility, but are also detrimental to human health and transportation. In order to develop a method to estimate PM 2.5 mass concentration from the widely measured visibility, a field campaign was conducted in Southwest China in January 2019. Visibility, ambient relative humidity (RH), PM 2.5 mass concentrations and scattering coefficients of dry particles were measured. During the campaign, two pollution episodes, i.e., from 4–9 January and from 10–16 January, were encountered. Each of the two episodes could be divided into two periods. High aerosol hygroscopicity was found during the first period, when RH was higher than 80% at most of the time, and sometimes even approached 100%. The second period experienced a relatively dry but more polluted condition and aerosol hygroscopicity was lower than that during the first period. An empirical relationship between PM 2.5 mass concentration and visibility (ambient aerosol extinction) under different RH conditions could thus be established. Based on the empirical relationship, PM 2.5 mass concentration could be well estimated from visibility and RH. This method will be useful for remote sensing of PM 2.5 mass concentration.